Emergence and genomic epidemiology of tigecycline resistant bacteria of fly origin across urban and rural China - Zelin Yan; Panpan Wang; Hanyu Wang; Jing Zhang; Yanyan Zhang; Yuchen Wu; Hongwei Zhou; Yan Li; Zhangqi Shen; Gongxiang Chen; Ruichao Li; Rong Zhang (Environment International)
Plasmid-mediated tigecycline resistance genes, notably the tet(X) and tmexCD-toprJ genes, have garnered considerable attention due to their transferability. This study aims to investigate the prevalence and resistance mechanisms associated with tet(X) and tmexCD-toprJ in flies, which are important reservoirs of antimicrobial resistance genes. A total of 52 tigecycline resistant bacterial isolates were collected, among which 40 (76.9 %) and 12 (23.1 %) were positive for tet(X) and tmexCD-toprJ, respectively. Tigecycline resistant bacteria were isolated from diverse geographical locations in China, with tet(X4)-positive Escherichia coli and tmexCD1-toprJ1-positive Klebsiella pneumoniae dominant among the isolates. The prevalence of tet(X) in rural area was significantly higher than that in urban area (2.7 % vs. 0.3 %; P < 0.001), while the prevalence of tmexCD1-toprJ1 shows no significant difference between urban and rural areas (0.2 % vs. 0.6 %; P > 0.05). Most tet(X)-positive strains (n = 40, 100.0 %), and 11(91.7 %) of the tmexCD1-toprJ1-positive strains exhibited multi-drug resistance. The IncFIB(Mar)/IncHI1B hybrid plasmid carrying tmexCD1-toprJ1 was identified by whole-genome sequencing analysis, which dominated the transmission of tmexCD1-toprJ1 in K. pneumoniae. Genetic context analysis showed that tmexCD1-toprJ1 was related locally to IS26, and IS26 may exacerbate the spread of tmexCD1-toprJ1 in different bacteria. In addition, the genetic structure of tmexCD1-toprJ1 also contains several antimicrobial resistance genes, including aph(3′)-Ic, sul1, blaDHA-1, blaCTX-M−5, etc., conferring resistance to aminoglycosides, sulfonamides, and carbapenems. This study provides insights into the epidemiology and transmission dynamics of tigecycline resistance genes, informing targeted intervention strategies to mitigate antimicrobial resistance dissemination.